A Review of NLP Advances at ICLR 2026: Sparse Autoencoders and Memory-Augmented Agents - Ferreira, David O. C.; Posselt, Dárvin C.; Galvão Filho, Arlindo R. (Anais da Escola Regional de Informática do Triângulo Mineiro (ERI-TM), 2026)
The 2026 International Conference on Learning Representations (ICLR) served as a prominent venue for advances in representation learning, with a particularly strong track in Natural Language Processing (NLP). This review synthesizes the main contributions presented at the conference along two thematic axes that attracted significant attention: (1) the application of sparse autoencoders (SAEs) for model interpretability and faithful text generation, and (2) the design of memory-augmented architectures for more adaptive and context-aware language agents. By systematically examining works selected from the official proceedings, this paper provides a structured overview of the key methodological innovations within these themes. Subsequently, an analysis is presented on how the unsupervised nature of SAE-based approaches facilitates the development of hallucination detectors and interpretability tools, alongside a discussion of how emerging memory mechanisms enable agents to maintain consistency over extended interaction horizons. Through this synthesis, the review highlights the potential impact of these techniques on NLP and identifies outstanding challenges, with a special focus on their relevance and applicability to the Brazilian research community.